Reading the Juggler of Notre Dame Medieval Miracles and Modern Remakings - Ziolkowski, Jan (Open Book Publishers, 2022)
In this two-part anthology, Jan M. Ziolkowski builds on themes uncovered in his earlier The Juggler of Notre Dame and the Medievalizing of Modernity. Here he focuses particularly on the performing arts. Part one contextualises Our Lady's Tumbler, a French poem of the late 1230s, by comparing it with episodes in the Bible and miracles in a wide variety of medieval European sources. It relates this material to analogues and folklore across the ages from, among others, Persian, Jewish and Hungarian cultures. Part two scrutinizes the reception and impact of the poem with reference to modern European and American literature, including works by the Nobel prize-winner Anatole France, professor-poet Katharine Lee Bates, philosopher-historian Henry Adams and poet W.H. Auden. This innovative collection of sources introduces readers to many previously untranslated texts, and invites them to explore the journey of Our Lady's Tumbler across both sides of the Atlantic. Reading the Juggler of Notre Dame: Medieval Miracles and Modern Remakings will benefit scholars and students alike. The short introductions and numerous annotations shed light on unusual beliefs and practices of the past, making the readings accessible to anyone with an interest in the arts and an openness to the Middle Ages.